Discrimination of Metabolite Profiles of Gayo Roasted Arabica and Robusta Coffees - Nizar Happyana; Yana Maolana Syah; Euis Holisotan Hakim (Universitas Jenderal Soedirman, 2022)
Gayo (Aceh) coffee is one of the best coffees from Indonesia. In this work, metabolites in the Gayo roasted arabica and robusta coffees were identified with 1H NMR spectroscopy analysis. Accumulatively 28 compounds were successfully detected, including the major and minor metabolites of the roasted coffee. Multivariate data analysis was applied to evaluate the dataset extracted from 1H NMR spectra of the coffee samples, result in the disclosure of the differences in the chemical profiles between the Gayo roasted coffees of arabica and robusta. Score plots obtained from the models of principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLSDA), classified the roasted coffee samples based on their species. Loading plot and S-plot revealed the discriminant compounds for each coffee. Gayo roasted arabica coffee was characterized with acetic acid and trigonelline, while the robusta coffee was discriminated with fatty acids. This report revealed the chemical differences of both coffees and confirmed the diversity of Gayo coffees.